Language-independent aspect-oriented programming - CAHILL, VINNY (My University, 2003)
The term aspect-oriented programming (AOP) has come to describe the set of programming mechanisms developed specifically to express crosscutting concerns. Since crosscutting concerns cannot be properly modularized within object-oriented programming, they are expressed as aspects and are composed, or woven, with traditionally encapsulated functionality referred to as components. Many AOP models exist, but their implementations are typically coupled with a single language. To allow weaving of existing components with aspects written in the language of choice, AOP requires a language-independent tool. This paper presents Weave.NET, a load-time weaver that allows aspects and components to be written in a variety of languages and freely intermixed. Weave.NET relies on XML to specify aspect bindings and standardized Common Language Infrastructure to avoid coupling aspects or components with a particular language. By demonstrating language-independence, Weave.NET provides a migration path to the AOP paradigm by preserving existing developer knowledge, tools, and software components. The tool?s capabilities are demonstrated with logging aspects written in and applied to Visual Basic and C# components.
PUBLISHED
Object-Oriented Programming Systems, Languages and Applications (OOPSLA 2003),
Keywords: Aspect-oriented programming, Weave.NET, Common Language